An Innovative Investigation on Fluid-to-Fluid Modeling of Post-Dryout Heat Transfer in Thermal Energy Systems - Yu, Dali; Xu, Chi; Hu, Chongju; Fan, Yijiang (Frontiers in Energy Research, 2022)
Post-dryout heat transfer is an important thermal-hydraulic phenomenon happening in the loss of coolant accident (LOCA) of water-cooled nuclear reactors and the off-design conditions of water cooled ceramic breeder (WCCB) blanket in fusion reactors. It is necessary to research the flow and heat transfer mechanisms of Post-dryout. To economically and comprehensively study on the post-dryout heat transfer characteristics, this work conducted fluid-to-fluid modeling research on the water and R-134a databanks through using Buckingham dimensional analysis methodology. In addition, a new interpolation method was developed and verified to make the scaling between two databanks possible. Finally, a scaling method of post-dryout heat transfer was proposed and assessed by experimental data. Results showed that the obtained scaling method is reliable in certain conditions.